EVALUASI PENGUKURAN WEBSITE LEARNING MANAGEMENT SYSTEM MENGGUNAKAN METODE WEBQUAL 4.0 PADA SMK NEGERI 2 KURIPAN - Nasarudin; Wing Wahyu Winarno; Mei Parwanto Kurniawan (LPPM STMIK El Rahma Yogyakarta, 2021)
This study aims to evaluate the measurement of service levels and user satisfaction of theLearning Management System of SMK Negeri 2 Kuripan using the WebQual 4.0 method. To find outand identify the significant influence of the Learning Management System service quality on service qualityand user satisfaction with perceptions measured using the variables approach in WebQual 4.0.This study uses the Learning Management System website object at SMK Negeri 2 Kuripanwith the www.smkn2kuripan.id page, with a sample of 204 respondents, namely teachers and students.the method used to evaluate the calculation of perception with the WebQual approach and variables aswell as the calculation of multiple linear regression analysis and science. The results of the study indicate that there is a positive and significant and insignificantrelationship between the variables of website service quality. level of satisfaction. and intensity of use thatform the conceptual model of the study. So to improve service quality and user satisfaction. it is necessaryto maintain consistency in service performance by conducting periodic evaluations and perceptualinteractions with users. And what needs to be considered is related to the ease of Usability. InformationQuality. and Service Interaction Quality on the website. The results of the research are expected to helpthe website manager of SMK Negeri 2 Kuripan to evaluate improvements and develop service qualityimprovements based on user responses/perceptions in accordance with the expectations of users of SMKNegeri 2 Kuripan.